FROM COMPLIANCE TO CARE: RECONSTRUCTING FEMINIST ACCOUNTABILITY IN GLOBAL AID GOVERNANCE - Pangeran, Andi; Soetjipto, Ani Widyani; Adelina, Shelly (UI Scholars Hub, 2026)
This article critically examines the literature on global aid governance through a feminist lens, focusing on three key areas: epistemic power, organisational depoliticisation, and the ethics of accountability. The review reveals that the coloniality of knowledge in global aid governance creates epistemic hierarchies grounded in claims of objectivity and efficiency, thereby marginalising local voices. Meanwhile, processes such as NGO-isation and professionalisation have transformed activism into administrative compliance. However, within these structures, reflective agency can still emerge through negotiated autonomy and the politics of translation, allowing feminist organisations to maintain their political significance. Regarding ethics, feminist accountability is redefined as a relational practice that opposes the neoliberal model of accountability and emphasises collective responsibility rooted in trust, solidarity, and collective reflection. This review advances a framework of decolonial accountability, shifting from surveillance to collective responsibility, from mere compliance to reflective engagement, and from hierarchical domination to equitable relationships in the context of global aid governance.